School and family, two sides of the same coin: for a necessary alliance for the prevention of gender stereotypes in adolescence - Villar Varela, Milena; Barreiro Fernández, Felicidad; García Sánchez, Alba María (Revista Complutense de Educación, 2024)
Gender stereotypes permeate the collective imagination of society, in general, and of adolescence, in particular, due, in part, to the differentiated socialization exercised by the family and the educational system. Taking into account the foregoing, the work presented has as fundamental objectives to examine the presence of sexist stereotypes, in the family environment and in the academic field, in the students who attend Compulsory Secondary Education in the Autonomous Community of Galicia and to analyze the possible existence of statistically significant differences based on sex, in said stereotypes. For this, a non-experimental design of a cross-sectional nature, of a descriptive nature, has been used, through an instrument elaborated ad hoc and applied to a sample of 379 students of Compulsory Secondary Education (50.7% boys and 49.3% girls). . The results show that, although the students present a good disposition towards gender equality, this is much more accentuated in the female students than in the male students, in the two areas under study (family and academic). These results will make it possible to establish guidelines for action, both from the academic sphere and from the family sphere, so that both socialization agents can act cooperatively in the eradication of gender stereotypes.